Fabrication of the AgI/BiOI/BiPO4 multi-heterojunction with high photocatalytic activity. (June 2020) - Long, Yanju; Li, Lingxin; Zhou, Luting; Zhang, Sifeng; Wang, Lulu; Zheng, Ziguang; Wu, Shenglan; Hei, Yunrui; Jiang, Fengzhi
Graphical abstract: The cartoon of formation procedure of the AgI/BiOI/BiPO4 microspheres (a) and and the possible degradation processes over n-p-n AgI/BiOI/BiPO4 heterojunction (b). Highlights: The ternary heterojunction AgI/BiOI/BiPO4 photocatalyst was synthesized by ion exchange at room temperature. The formation of ternary heterojunction AgI/BiOI/BiPO4 is beneficial for lowing the recombination rate of electron-hole pairs. Under visible light, AgI/BiOI/BiPO4 photocatalyst could achieve rapid degradation of 17α-ethynylestradiol (EE2). Abstract: 17α-acetylestradiol (EE2) as an environmental endocrine disruptor (EDCs) with strong estrogenic effect and stable chemical properties. Water treatment technologies involving photocatalytic decomposition of pollutants technology are widely used to degrade pollutants in water, having excellent research value and good applicability prospects. A series of photocatalysts (AgI/BiOI/BiPO4, AgI/BiOI and AgI/BiPO4 ) were prepared by a ion exchange route at room temperature and analyzed by different characterization methods. The results showed that AgI/BiOI/BiPO4 exhibited excellent properties: (1) improved visible light photoresponse, (2) improved stability and (3) reduced recombination rate of electron-hole pairs. AgI/BiOI/BiPO4 showed excellent photodegradation activity for the 17α-ethynylestradiol (EE2): The removal rate of EE2 was close to reach 100 % in 8 min under visible light. The value of reaction rate constant of AgI/BiOI/BiPO4 (2:2:2) was 11.5, 5.6, 2.5 and 1.7 times higher than AgI, BiOI, AgI/BiOI, and AgI/BiPO4, respectively. Finally, the possible photocatalytic mechanism of the AgI/BiOI/BiPO4 multiheterojunction was proposed.